Praktik Persaingan Usaha Tidak Sehat antara Toko Modern dan Pasar Tradisional dalam Ketidaksesuaian Jarak sebagaimana diatur dalam Perda Kota Palangka Raya No. 17 Tahun 2014 tentang Toko Modern - Perti Gina; Mulida Hayati Hayati; Elin Sudiarti; Rollys Suriani (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines unfair business competition between modern retail stores and traditional markets in Palangka Raya City due to non-compliance with minimum distance regulations under Regional Regulation No. 17 of 2014. Using an empirical, and regulatory analysis. The results show that the rapid expansion of modern retail outlets often violates zoning requirements, causing financial losses and business closures among traditional traders, alongside weak local government supervision. Consistent regulatory enforcement is required to ensure fairness and sustainable local economic development.